English Teacher’s Representations of the Comprehensive Training Process: How Do They Describe It? - Díaz Monsalve, Ana Elsy; Carmona Agudelo, Nadia Carolina (Íkala, Revista de Lenguaje y Cultura, 2010)
In order to identify perceptions of comprehensive learning held by public elementary school English teachers in Medellín, nineteen teachers with undergraduate or graduate degrees in English participated in a qualitative study, completed a questionnaire, and some took part in an in-depth interview. English teacher perceptions possess both practical and theoretical characteristics and are structured thematically in accordance with student personality, communicative ability, and social and cultural context. This research project allowed the authors to create new concepts of comprehensive learning based on the experiences of English teachers. Received: 31-08-09/ Accepted: 09-12-09 How to reference this article: Diaz Monslve, A. E. & Carmona Agudelo, N. C. (2010). Representaciones de los docentes de inglés sobre el proceso de formación integral: ¿qué descripción ofrecen de ella? Íkala. 15(1), pp.173-203.